Memorandum of agreement between UiTM Sarawak and Malaysia Airports Bhd - Kipli, Nur Aida; Ramakrishnan, Prabha; Maniam, Yuthandy; Abdullah, Norazlin; Jack, Suriani; Abg Samah, Aizimah; Chiew, Fei Ha (Universiti Teknologi MARA, Sarawak, 2009)
A Memorandum of Agreement between Universiti Teknologi MARA Sarawak (UiTMS) and Malaysia Airports Holdings Berhad (MAHB) was held on the 1st July 2008 at Crowne Plaza Hotel, Kuching. This memorandum was signed for the 30 MAHB executives who are currently undergoing the program of Executive Diploma in Management which was tailored-made for MAHB executives starting January 2008. This program comprises 9 modules which are to be completed in one year. The program will be another value-added knowledge and skill for the executives of MAHB as to prepare them to be future leaders that are well equipped with management skills trained by experienced and qualified lecturers from UiTMS. It signifies that MAHB trusted and accredited UiTMS as one of the leading institutions of higher learning.